Analisis Kesalahan Pemecahan Masalah Matematika pada Siswa Kelas V Sekolah Dasar - Daniel Fernando Tua Simanjuntak; Jennita Mairany; Rahma Ayuni; Muhammad Ahyar Fadli Siregar; Elvy Mailani; Nur Rarastika (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
This research aims to analyze the types of errors made by fifth grade elementary school students in solving mathematical problems. This research uses a qualitative descriptive method with a case study approach. The research subjects were 25 students who were selected based on the criteria of various academic abilities and difficulties in problem solving. Data was collected through mathematical problem solving tests, semi-structured interviews, and observations. The research results showed that students' errors in solving mathematical problems were divided into three types, namely: conceptual errors (44%), procedural errors (36%), and calculation errors (20%). Conceptual errors occur due to students' lack of understanding of basic mathematical principles, such as fractional number operations. Procedural errors are caused by students' ignorance in determining systematic steps to solve problems. Meanwhile, calculation errors arise due to students' low accuracy and concentration. This research recommends using a problem-based learning approach and interactive media to increase students' understanding of concepts. Apart from that, providing varied practice questions and feedback can help students correct their mistakes. Thus, students' mathematical problem solving abilities are expected to increase significantly.